Trappers of the Far West : sixteen biographical sketches - Hafeny, LeRoy R. ;Carter, Harvey L. (London, United Kingdom : University of Nebraska Press, 1983)
The book was enthusiastically received, as well it might have been, since it made available eighteen sketches. The present book contains sixteen short biographies of trappers and traders almost equal in renown to those of the previous book.
Introduction -- Etienne Provost -- James, Ohio Pattie -- Louis Robidoux -- Ewing young -- David Jackson -- Milton Sublette -- Lucien Fontenelle -- James Clyman -- James P. Beckwourth.
Includes index.
Keywords: WEST(US) -- HISTORY -- TO 1848 -- BIOGRAPHY -- ADDRESSES, ESSAYS, LECTURES